The 1st International Electronic Conference on Forests—Forests for a Better Future: Sustainability, Innovation, Inter 2020
DOI: 10.3390/iecf2020-07881
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Rope-Based Ascending Techniques and Materials of Professional Arborists in Italy

Abstract: The techniques funded for rope-based access to the tree canopy (the so-called tree climbing) have been spreading in recent years. A variety of practices, such as pruning, felling of trees, cabling, phytosanitary inspections, and others, can be carried out using these techniques, and the methods allow one to operate on trees placed in any location, proving extremely suitable for maintaining trees grown in an urban environment. In Italy, the number of arborists operating with a rope on trees is increasing signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Utilizing hemp rope as a tree-felling assistance in agroforestry based private forests can be considered an appropriate technique for protecting and preserving the remaining stands. According to Bianchini et al (2021), the use of ropes in the assist-felling technique is appropriate for sustaining tree growth in harsh environments. In addition, Cedergren et al (2002) and Nikooy et al (2013) proposed that the issue of minimizing the damage to the remaining stands caused by tree felling can be resolved by employing an appropriate felling technique and making felling instruments readily available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Utilizing hemp rope as a tree-felling assistance in agroforestry based private forests can be considered an appropriate technique for protecting and preserving the remaining stands. According to Bianchini et al (2021), the use of ropes in the assist-felling technique is appropriate for sustaining tree growth in harsh environments. In addition, Cedergren et al (2002) and Nikooy et al (2013) proposed that the issue of minimizing the damage to the remaining stands caused by tree felling can be resolved by employing an appropriate felling technique and making felling instruments readily available.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in ineffective time can be accomplished by implementing a systematic work method, well planning, and organization . Campu et al (2020) and Bianchini et al (2021) reported that the success of rope-raising tool utilization in tree felling is determined by: a) professional training and formation, b) work organization, and c) utilization of appropriate materials and equipment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental scheme consists of 36 overall tests carried out with 2 types of rope, on which 2 types of friction hitches were applied with special lanyards. Two friction hitches were chosen: the Prusik and the Valdotain hitch [8,17,24]. For each type of rope/knot, 3 pieces of rope and 3 cords were used.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most commonly used knots is the Valdotain tresse hitch (one-way knot) [17], and one of the most studied knots is the prusik (two-way knot) [18,19]. The prusik is a two-way friction hitch (it can be used in both directions of the string) that can be used to create movable anchor points on both double ropes and single ropes.…”
Section: Introductionmentioning
confidence: 99%